Efektifitas Pembinaan Kader Kesehatan Remaja (KKR) tentang TRIAS UKS terhadap Upaya Pencegahan Kenakalan Remaja pada Siswa Tingkat SMA/MA - Muhammad Al Amin; Achmad efendi; Pipit Hariyono; Akhmad Yanuar Fahmi Pamungkas (PROFESSIONAL HEALTH JOURNAL, 2019)
UKS is an education and health effort that is carried out in an integrated, conscious, planned, directed, and responsible manner in instilling, growing, developing, and guiding to live, enjoy, and implement the principles of healthy life in the lives of everyday students (Ahmad Selvia, 2009: 1). Based on the problems and research objectives to be achieved, this type of research is preexperimental research in the form of a "one-group pre-post test" design. The target population in this study were all students and high school / MA students in the working area of Srono District, Banyuwangi Regency, amounting to 1,841 people. The sample in this study were some students and high school / MA students in the working area of Srono District, Banyuwangi District who met the inclusion criteria as many as 1,248 respondents. The sampling technique used in this study was Purposive sampling. From the results of the bivariate statistical test using the Wilcoxon Test analysis obtained p value <0.05 which is equal to 0,000. From the results of these calculations, it can be concluded that there is an influence between the formation of adolescent health cadres (KKR) on prevention efforts for juvenile delinquency in high school / MA / SMK level students in the Srono District work area in Banyuwangi Regency in 2016. Providing a good environment early on, along with an understanding of the development of our children well, will help reduce juvenile delinquency, so families, parents and the community are expected to be able to find a good strategy to protect their children from juvenile delinquency can damage their future.